A ligand anchored conjugate adsorbent for effective mercury(II) detection and removal from aqueous media - Abbas, K.; Znad, Hussein; Awual, R. (Elsevier BV, 2018)
In this study, a novel mesoporous conjugate adsorbent (MCA) was fabricated by directly anchoring the organic ligand of 2-hydroxyacetophenone-4N-pyrrolidine thiosemicarbazones (HAPT) onto highly ordered mesoporous ZSM-5 for efficient and selective mercury (Hg(II)) ions capturing from aqueous solution. The effect of solution pH, interference of foreign metal ions, contact time, initial Hg(II) ions concentration, and elution-regeneration of the MCA were evaluated in the case of detection and removal operations. The MCA was exhibited an obvious color change from colorless to yellow in the presence of Hg(II) ions at optimum pH conditions. In addition, the Hg(II) ions was detected and removed from water samples with naked-eye observations. The sensitive detection was determined under specific optimum conditions and the lower detection limit was determined by the MCA was 3.69 µg/L of Hg(II) ions. The foreign ions effect was evaluated and the MCA was exhibited high selectivity towards the Hg(II) ions with optimum color formation and the Hg(II) ions can be detected easily on-site Hg(II) ions monitoring. The adsorption efficiency was determined in terms of initial Hg(II) ions concentration. The data well fitted with the Langmuir isotherm model, and the maximum adsorption capacity of Hg(II) ions was 172.61 mg/g by the MCA. Moreover, the adsorption results of the MCA were compared with the other forms of different materials. The effective eluent of 0.10 M thiourea-0.10 M HCl was used to elute the Hg(II) ions from the MCA, and the MCA was simultaneously regenerated into the initial form for next process without significant loss in its initial performance. The data clarified that the MCA is an efficient and eco-friendly for simultaneous detection and removal of Hg(II) ions from wastewater samples.